2002
DOI: 10.1002/mrc.1117
|View full text |Cite
|
Sign up to set email alerts
|

PGSE NMR diffusion study of the self‐association of N‐methylacetamide in carbon tetrachloride

Abstract: N-Methylacetamide (NMA) is known to self-associate in solution through the formation of hydrogen bonds. This behavior, and the presence in the molecule of an amide bond, make this an interesting model for study since the oligomer can be considered to be a protein analogue. The aims of the present study were to estimate the thermodynamic parameters of the self-association process, through the measurement of the diffusion coefficient of NMA in carbon tetrachloride (CCl 4 ), and to predict the population distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In both studies it was found that initial dimerization was less favorable compared to subsequent elongation, indicating a cooperative supramolecular polymerization. Further thermodynamic studies on the self-association of N-methylacetamide in apolar solvents probed using dielectric spectroscopy, 347 FT-IR, 348 and PGSE NMR diffusion 349 measurements have shown the generality of the results obtained by Davies, Thomas, and LaPlanche. On the basis of the values of the dimerization and elongation equilibrium constant that were reported in these studies, σ values between 10 -1 and 10 -3 can be calculated for systems that polymerize via amide type hydrogen bonds.…”
Section: Electronic Effectsmentioning
confidence: 58%
“…In both studies it was found that initial dimerization was less favorable compared to subsequent elongation, indicating a cooperative supramolecular polymerization. Further thermodynamic studies on the self-association of N-methylacetamide in apolar solvents probed using dielectric spectroscopy, 347 FT-IR, 348 and PGSE NMR diffusion 349 measurements have shown the generality of the results obtained by Davies, Thomas, and LaPlanche. On the basis of the values of the dimerization and elongation equilibrium constant that were reported in these studies, σ values between 10 -1 and 10 -3 can be calculated for systems that polymerize via amide type hydrogen bonds.…”
Section: Electronic Effectsmentioning
confidence: 58%
“…In a solution in which the solute does not associate, it is expected that the selfdiffusion coefficient will be independent of the concentration. [9] As it can be seen from at the highest concentration of 2 and 4, respectively. This behaviour confirms that an aggregation phenomenon occurs.…”
Section: Resultsmentioning
confidence: 84%
“…The PGSE NMR diffusion measurements were carried out by using the stimulated echo pulse sequence,18b as has been explained elsewhere 17c. 28 All the experiments were performed on a 500 MHz Bruker AVANCE spectrometer, equipped with a microprocessor‐controlled gradient unit and a multinuclear inverse probe with an actively shielded Z‐gradient coil.…”
Section: Methodsmentioning
confidence: 99%